2014
DOI: 10.1590/1414-431x20133358
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated Parapoxvirus ovis induces a transient increase in the expression of proinflammatory, Th1-related, and autoregulatory cytokines in mice

Abstract: The immunostimulatory properties of inactivated Parapoxvirus ovis (iPPVO) have long been investigated in different animal species and experimental settings. In this study, we investigated the effects of iPPVO on cytokine expression in mice after intraperitoneal inoculation. Spleen and sera collected from iPPVO-treated mice at intervals after inoculation were submitted to cytokine mRNA determination by real-time PCR (qPCR), serum protein concentration by ELISA, and interferon (IFN)-α/β activity by bioassay. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
1
15
1
2
Order By: Relevance
“…Our study also showed an increased IL-10 expression but no modulation of IL-1β and IL-6 mRNA. These results confirm that iPPVO stimulates the production of cytokines in equine PBMC as it was described in other species like murine, porcine, and human [ 39 , 42 , 43 ]. iPPVO was associated with stimulation of proinflammatory, Th1, and Th2 related cytokines (reviewed by [ 19 ]).…”
Section: Discussionsupporting
confidence: 89%
“…Our study also showed an increased IL-10 expression but no modulation of IL-1β and IL-6 mRNA. These results confirm that iPPVO stimulates the production of cytokines in equine PBMC as it was described in other species like murine, porcine, and human [ 39 , 42 , 43 ]. iPPVO was associated with stimulation of proinflammatory, Th1, and Th2 related cytokines (reviewed by [ 19 ]).…”
Section: Discussionsupporting
confidence: 89%
“…In terms of cellular immunity, the host antiviral defenses are activated by increasing granulocytes, accompanied by the recruitment of CD4+ T and CD8+ T cells, while the recruitment of B cells and DC need the assistance of MHC molecules . As shown in Figure , ORFV induces mainly the Th1 immune response at the early stage of infection . The peripheral immune cells secrete IFN‐γ, TNF‐α, IL‐6, IL‐8, IL‐12, and IL‐18, after which the Th2 type immune response appears, mainly inducing the secretion of IL‐4, IL‐10, and IL‐1 receptor antagonists (IL‐1RA) .…”
Section: Virulence Genes and Immunomodulatory Ability Of Orfvmentioning
confidence: 99%
“…The amount of TNF produced is the main factor for the control of its role in the disease process [ 2 ]. IL-6 is primarily synthesized by T and B lymphocytes and by some other cells [ 1 ]. IL-6 leads to synthesis of acute phase reactants (CRP, haptoglobulin, etc.…”
mentioning
confidence: 99%
“…1 ). It has been reported by Anziliero et al [ 1 ] that pro-inflammatory cytokines (TNF-α) reach to the peak level 24 hr after iPPOV inoculation in mice. Moreover, experimental models of infection (Lipopolysaccharide, LPS in rat) report that it reaches to higher concentrations in shorter times [ 26 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation